The unmet financial needs of intermediary firms within agri-food value chains in Uganda and Bangladesh - Adong, Annet; Ambler, Kate; Bloem, Jeffrey R.; de Brauw, Alan; Herskowitz, Sylvan; Islam, A.H.M. Saiful; Wagner, Julia (Elsevier, 2025)
Intermediary firms within agri-food value chains — operating between the farmgate and retailers — typically account for at least as much, if not more, value added as the primary agricultural production sector of the economy, but little is known about how these small and largely informal firms conduct their business. Drawing on a set of innovative surveys implemented amid the arabica coffee and soybean value chains in Uganda and the rice and potato value chains in Bangladesh, we describe the financial activities of these intermediary firms. We document four sets of results. First, across all intermediary actors in our data the overwhelming majority of transactions are cash-based. Second, although many intermediary actors are un-banked, access to financial accounts varies considerably by value chain segment, commodity, and country. Third, while most intermediary actors report using mobile money for personal purposes, especially in Uganda, very few use mobile money to facilitate business transactions. Fourth, although intermediary actors frequently report exposure to risk, very few effectively manage this risk. We conclude by discussing how intermediary agri-food value chain actors represent an underappreciated population for the promotion of new technologies to improve outcomes among both intermediary actors themselves and smallholder farmers.